Clinical mastitis associated with Arcanobacterium spp. infection in a Boer cross goat - Abdullah, Faez Firdaus Jesse; Mohammed, Konto; Abba, Yusuf; Tijjani, Abdulnasir; Adamu, Lawan; Osman, Abdinasir Yusuf; Saharee, Abdul Aziz; Haron, Abd Wahid (Global Researchers Journals, 2014)
A 2 year old Boer cross doe was presented to the University Veterinary Hospital, Faculty of Veterinary Medicine, Universiti Putra Malaysia with a swollen and firm left mammary gland. The vital parameters were within the normal range. On physical examination, the left mammary gland and inguinal lymph node were enlarged with presence of multiple nodules on palpation. Aspiration of the gland produced a thick chessy exudate. Milk and blood samples were aseptically collected and sent to the laboratory for bacterial isolation and culture and haematological evaluation, respectively. The bacterial culture yielded the growth of Arcanobacterium spp, while the haematological evaluation showed leucocytosis with neutrophilia, monocytosis and eosinophilia. Diagnosis was based on clinical signs, haematological evaluation and bacteriological culture results. Norocillin 25mg/ kg i.m stat (Norbrook laboratories, New Zealand) and intramammary infusion of Procaine penicillin (PenjectR, Butler Schein™ Animal Health) at 400 IU/kg were administered, followed by Flunixin meglumine 1.1mg/kg i.m (Norbrook laboratories, New Zealand) and multivitamin injection 10mg/kg i.m (Norbrook laboratories, New Zealand) for 5 days. The prognosis was poor after a week as the goat did not respond to the treatment. The farmer was advised to cull the animal in order to avoid further expenses and eliminate the risk of transmission to other does in the herd.